To solve the equation \( 2x - 5 = 3(4x + 5) \), the steps can be arranged as follows:
Step 1: Distributive Property to get
Use the distributive property to expand the right side of the equation: \[ 2x - 5 = 3 \cdot 4x + 3 \cdot 5 \quad \Rightarrow \quad 2x - 5 = 12x + 15 \]
Step 2: Addition of Equality Property to get
Add 5 to both sides of the equation to isolate the terms involving \( x \): \[ 2x - 5 + 5 = 12x + 15 + 5 \quad \Rightarrow \quad 2x = 12x + 20 \]
Step 3: Combine Like Terms Property to get
Subtract \( 12x \) from both sides of the equation: \[ 2x - 12x = 20 \quad \Rightarrow \quad -10x = 20 \]
Step 4: Division of Equality Property to get
Divide both sides by -10 to solve for \( x \): \[ x = \frac{20}{-10} \quad \Rightarrow \quad x = -2 \]
So, the ordered steps for solving the equation are:
- Step 1: Distributive Property to get \( 2x - 5 = 12x + 15 \)
- Step 2: Addition of Equality Property to get \( 2x = 12x + 20 \)
- Step 3: Combine Like Terms Property to get \( -10x = 20 \)
- Step 4: Division of Equality Property to get \( x = -2 \)
This is the correct order of steps to solve the equation.